Wavelength dependence of dark adaptation in Phycomyces phototropism (The Rockefeller University Press, 1984)
The wavelength dependence of phototropic dark adaptation in Phycomyces was studied between 347 and 545 nm. Dark adaptation kinetics were measured for wavelengths of 383, 409, 477, and 507 nm in the intensity range from 6.2 X 10(-2) to 2 X 10(-7) W X m-2. At these wavelengths, dark adaptation follows a biexponential decay as found previously with broadband blue light (Russo, V. E. A., and P. Galland, 1980, Struct. Bonding., 41:71; Lipson, E. D., and S. M. Block, 1983, J. Gen. Physiol., 81:845). We have found that the time constants of the fast and slow components depend critically on the wavelength. At 507 nm, dark adaptation kinetics were found to be monophasic. The phototropic latency after a step down by a factor of 500 was measured for 19 different wavelengths. Maximal latencies were found at 383, 477, and 530 nm; minimal latencies were found at 409 and 507 nm. With irradiation programs that employ different wavelengths before and after the step down, the dark adaptation kinetics depend critically on the sequence in which the two wavelengths are given. We have found too that not only do the adaptation kinetics vary with wavelength, but so also do the phototropic bending rate and the phototropic latencies in experiments without intensity change. The results imply that more than one photoreceptor is mediating phototropism in Phycomyces and that sensory adaptation is regulated by these photoreceptors.